The Role of Technology in Policy Dynamics: The Case of Desalination in Israel. (18th April 2013) - Teschner, Naama; Garb, Yaakov; Paavola, Jouni
ABSTRACT: This article examines the relationship between technology and policy change, focusing on shifts in Israel's water regime as a case example. Technologies, especially systems of large‐scale infrastructures, have offered an explanation for the stability and stagnation of policy regimes in what has been termed "lock‐in" and path dependency. Our paper focuses on the reverse phenomenon: on how technology or change in it can induce policy change. Israeli decision‐makers have recently embraced desalination technology as a substitute for natural resources, because earlier policies, characterized by a strategy of environmental brinkmanship, have resulted in degradation of natural sources and risk future supply. This analysis is based on extensive document analysis and in‐depth interviews. We suggest that technological breakthroughs that rendered desalination economically feasible also undermined long‐lasting hydro‐ideological support for agriculture, introduced new ideas about water abundance and engendered policy change. Desalination contributed to these shifts because it allowed the displacement of environmental externalities, economic costs and hard political choices to other policy sectors and levels of governance as well as reallocating them between political actors, bureaucrats and professionals. It is important to make displacements like these more visible in order to emphasize more comprehensive and longer‐term problem solving rather than problem avoidance or postponement. Copyright © 2013 John Wiley & Sons, Ltd and ERP Environment.